Fibrillar extracellular matrix produced by pericyte-like cells facilitates glioma cell dissemination - Vymola, Petr; Garcia-Borja, Elena; Cervenka, Jakub; Balaziova, Eva; Vymolova, Barbora; Veprkova, Jana; Vodicka, Petr; Skalnikova, Helena; Tomas, Robert; Netuka, David; Busek, Petr; Sedo, Aleksi (Brain pathology (Zurich, Switzerland), 2024)
Gliomagenesis induces profound changes in the composition of the extracellular matrix (ECM) of the brain. In this study, we identified a cellular population responsible for the increased deposition of collagen I and fibronectin in glioblastoma. Elevated levels of the fibrillar proteins collagen I and fibronectin were associated with the expression of fibroblast activation protein (FAP), which is predominantly found in pericyte-like cells in glioblastoma. FAP+ pericyte-like cells were present in regions rich in collagen I and fibronectin in biopsy material and produced substantially more collagen I and fibronectin in vitro compared to other cell types found in the GBM microenvironment. Using mass spectrometry, we demonstrated that 3D matrices produced by FAP+ pericyte-like cells are rich in collagen I and fibronectin and contain several basement membrane proteins. This expression pattern differed markedly from glioma cells. Finally, we have shown that ECM produced by FAP+ pericyte-like cells enhances the migration of glioma cells including glioma stem-like cells, promotes their adhesion, and activates focal adhesion kinase (FAK) signaling. Taken together, our findings establish FAP+ pericyte-like cells as crucial producers of a complex ECM rich in collagen I and fibronectin, facilitating the dissemination of glioma cells through FAK activation.
Keywords: Brain Neoplasms; Tumor Microenvironment; membránové proteiny; nádorové buněčné linie; Cell Movement; nádorové mikroprostředí; Glioblastoma; Membrane Proteins; pericytes; gliom; pericyty; serinové endopeptidasy; fibronektiny; želatinasy; Collagen Type I; Glioma; Cell Line, Tumor; Endopeptidases; kolagen typu I; glioblastom; collagen type I; Extracellular Matrix; endopeptidasy; Gelatinases; fibronectin; proteomics; Fibronectins; Humans; pohyb buněk; glioblastoma; nádory mozku; Serine Endopeptidases; Pericytes; extracelulární matrix; lidé; extracellular matrix proteins